PENGELOLAAN STRES PADA KELUARGA KORBAN BENCANA LONGSOR DI KABUPATEN BOGOR - Sunarti, Euis; Syahrini, Junita Sari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2011)
This research focused to analyze family stress management of landslide’s victims of Banyuwangi village, Bogor District. This research used cross-sectional design, involved 100 families who became the victims of Banyuwangi village’s landslides as samples. Results showed that stressors which gave the greatest impact on family life wereintrafamily and finances/business strains.The correlation test showed the higher the level of finances and business strains, work transitions and strains, the lower the level of family hardiness and the higher the level of family stress. Meanwhile, the higher the level of marital strains, the lower the level of family coherence and the higher the level of family stress. The higher the level of family social support, then the higher the level of family coherence and family coping strategy. The regression test indicated that family stress of landslide’s victim was influenced by stressor, family hardiness, and coping strategy focused on problem.